Pengaruh electronic word of mouth (e-wom) dan customer engagement terhadap keputusan pembelian pada urban & co di banjarmasin - Juwita Wardani; Devi Rusvitawati; Muhammad Fathoni; Nurul Wahyuni (Business Administration, FISIP ULM, 2026)
This study seeks to analyze the effect of Electronic Word of Mouth and Customer Engagement, both individually and simultaneously, on purchasing decisions at Urban & Co in Banjarmasin. A quantitative research approach was applied with a total of 105 respondents. The sample was selected using purposive sampling based on the Cochran formula. Data were collected through questionnaires and then examined using multiple linear regression analysis with the assistance of SPSS version 22 software. The findings indicate that Electronic Word of Mouth and Customer Engagement significantly influence purchasing decisions, both partially and simultaneously, at Urban & Co in Banjarmasin..